Early childhood cortisol reactivity moderates the effects of parent–child relationship quality on the development of children's temperament in early childhood. Issue 3 (21st December 2015) - Kopala‐Sibley, Daniel C.; Dougherty, Lea R.; Dyson, Margret W.; Laptook, Rebecca S.; Olino, Thomas M.; Bufferd, Sara J.; Klein, Daniel N.
Abstract: Positive parenting has been related both to lower cortisol reactivity and more adaptive temperament traits in children, whereas elevated cortisol reactivity may be related to maladaptive temperament traits, such as higher negative emotionality (NE) and lower positive emotionality (PE). However, no studies have examined whether hypothalamic‐pituitary‐adrenal axis activity, as measured by cortisol reactivity, moderates the effect of the quality of the parent–child relationship on changes in temperament in early childhood. In this study, 126 3‐year‐olds were administered the Laboratory Temperament Assessment Battery (Lab‐TAB; Goldsmith et al ., 1995) as a measure of temperamental NE and PE. Salivary cortisol was collected from the child at 4 time points during this task. The primary parent and the child completed the Teaching Tasks battery (Egeland et al ., 1995), from which the quality of the relationship was coded. At age 6, children completed the Lab‐TAB again. From age 3 to 6, adjusting for age 3 PE or NE, a better quality relationship with their primary parent predicted decreases in NE for children with elevated cortisol reactivity and predicted increases in PE for children with low cortisol reactivity. Results have implications for our understanding of the interaction of biological stress systems and the parent–child relationship in the development of temperament in childhood. Abstract : In the current study, a better quality parent‐child relationship predicted increases in PE in less reactive children, whereas a poorer quality relationship predicted increases in NE for more highly reactive children.